A New Editor-in-Chief for Land - Andrew Millington (Land, 2021)
In writing this editorial, I am signing off as the founding Editor-in-Chief of Land, and it is with great pleasure that I am handing over these duties to Professor Christine Fürst, who has been Section Editor-in-Chief of the Section “Landscape Ecology” since 2020 [...]